INDEKS MENTAL-KOGNITIF ISLAM: SATU PENANDA ARAS PSIKOSPIRTUAL ISLAM REMAJA BERISIKO - Khairil Anwar (AL-FIKRA, 2015)
The purpose of this study was to describe the Islamic Mentalcognitive index on risk youth. Islamic Mental-cognitive termed a structure depths of human childbirth perception, introspection, memory, creativity, imagination, conception, belief, reasoning, volition, and emotions as a unified way of thinking based on Islam, is an attempt to predict and as approaches to identify the problem and solve psychological risk youth. Six recovery centers have been chosen for this study, involving busy as 490 coaches and 128 students of a secondary school of nationality as a collection of the convoy. Background to the economic status of parents of respondents also identified and data collection is done using inquired about the accreditation forms which contains a measurement of Islamic Mental-cognitive. Data were analyzed using a mathematical formula to form the Islamic Mental-cognitive index that consists of multiple domains. Decision of the study showed an index of Islamic Mental-cognitive is at the stage of a low (score 51.56). The discovery of this study backs up one module coaching intervention and prevention against socio-psychological symptoms teens through the principles of the concept of Islamic Mental-cognitive, Islamic psychosocial and sunnah behavior.